Usage of Information in Strategic Management Process with a Reference to Small and Medium Sized Enterprises of Bihar: Examining the Implementation and Effectiveness of Strategic Management Principles in Small and Medium-sized Enterprises in Bihar (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Strategic management is a current direction of management types. It is applied in all types of businesses, including small and medium-sized enterprises. However, the use of its principles is limited in SMEs. The limits are caused by the size of these enterprises related to greater focus on operational management. For SMEs, cumulating of functions is also typical oral communication is more common than written, etc. Despite those limitations, implementation of strategic principles in the management of SMEs is able to increase their competitiveness, reduce costs, improve decision-making, facilitate the introduction of employee motivation, shorten delivery times, provide better customer care, etc. The paper discusses whether and to what extent SMEs implement the principles of strategic management and whether its use is effective. The basic principle of strategic management is the formulation and selection of a strategy.